The influence of work discipline, employee competence and information system on the efficiency of outpatient administration services for BPJS participants at Kendari Bhayangkara Hospital - Christina Mariet Naressy; Nani Yuniar; Kamrin Kamrin (PT WIM Solusi Prima, 2026)
Efficiency in administrative services is an important factor in improving the quality of population services, especially outpatient services for BPJS employees. The purpose of this study was to analyze the impact of work discipline, employee competence, and information systems on the effectiveness of outpatient administrative services for BPJS participants at Bhayangkara Hospital Kendari. This study used a quantitative cross-sectional approach. The population in this study were all hospital administrative employees, using a total sampling technique. Data analysis was performed using univariate analysis, bivariate analysis using chi-square analysis, and multivariate analysis using logistic regression. The results showed a significant impact of work discipline (p = 0.002), employee competence (p = 0.014), and information systems (p = 0.012) on the effectiveness of outpatient administrative services for BPJS participants. Together, these three variables influenced the effectiveness of administrative services, with work discipline being the most important variable. This indicates that as work discipline, employee competence, and the information systems used increase, the level of administrative service efficiency also increases. The conclusion of this study is that work discipline, employee competence, and information systems significantly influence the effectiveness of outpatient administrative services for BPJS employees. Therefore, it is necessary to improve employee discipline, develop competencies through training, and optimize information systems to increase the efficiency of home services.